Medication use in the neonatal intensive care unit in a tertiary hospital in China from 2020 to 2023 - Yi Wang; Linhong Song; Yanhua Wang; Jun Li; Yuanyuan Xie; Lei Yan; Huixia Zhou; Siqi Hu (Italian Journal of Pediatrics)
Abstract Background The use of medication in the neonatal intensive care unit (NICU) is a complex field that requires special attention, as neonatal patients may have different sensitivities and responses to drugs than adults and older children. The administration of medication in the NICU must consider various factors, including the dosage of the medication, the route of administration, monitoring, and potential drug interactions. Methods In this study, we conducted a retrospective analysis of medication use in the neonatal intensive care unit of 122 preterm infants treated in our hospital from 2020 to 2023. Results Correlation analysis revealed that among perinatal clinical characteristics, birth weight was moderately positively correlated with gestational age, with a correlation coefficient greater than that of birth weight with the Apgar score. The top 3 medication types in the NICU were “vitamins, nutritional drugs, enzyme preparations and drugs that regulate water, electrolytes, and acid-base balance”, “blood hematopoietic system medications”, and “antimicrobial medications”. From 2020 to 2023, the most commonly used drugs in the NICU were vitamin AD (vitamin A and vitamin D) drops and calcium gluconate injections. In addition, we demonstrated that the most commonly prescribed off-label drugs were vitamins, water and electrolyte balance nutrition drugs, and blood circulation system drugs. Conclusions Our retrospective study will not only help identify and evaluate interventions to reduce medication errors but also aid healthcare systems and providers in understanding, implementing, and enhancing these interventions to improve the safety and quality of care for newborns. Nonetheless, further research is needed to assess the relative cost-effectiveness of various medication safety interventions to facilitate their adoption and implementation in the decision-making process.